Physical Activity Levels in Brazilian Adolescents: A Secular Trend Study (2007–2017/18) - Pinto A.A. (2022)
© 2022 by the authors.Only a small proportion of Brazilian adolescents practice sufficient physical activity (PA). However, it is not clear whether this proportion has been decreasing over time. This study aimed to examine the 10-year trends of sufficient PA in adolescents and to investigate differences by sex and age. Using a standard protocol, we compared two cross-sectional cohorts of adolescents aged 15 to 18 years, recruited in 2007 (n = 1040) and in 2017/18 (n = 978). Using the International Physical Activity Questionnaire—Short Form (IPAQ-SF), the adolescents reported moderate-to-vigorous PA (MVPA) performed in the last seven days. Sufficient PA was defined as engaging in at least 60 min/day of MVPA. In the subgroups, investigated by sex or age, there was an increase in the prevalence of sufficient PA. Overall, sufficient PA declined by 28.1% from 2007 to 2017/18. Boys in 2007 were more active than their 2017/18 peers, and this was equally observed in girls in 2007 compared to those in 2017/18. The findings show decreasing secular trends in sufficient PA in the investigated adolescents. Not only are public health authorities in Brazil witnessing an escalation of insufficient PA, but they are also losing ground with the most active adolescents.